University as a matter of concern: on sharing and participating in a public university - Engemann, Anke (Ethics and education, 2025)
Engaging with current protests for climate justice on university campuses, this paper discusses how matters of concern are shared in the university and how cohabitation on campus itself becomes a public matter. Multiple ecological and political crises shed light on the interdependence between the public and the communal dimension of university. Drawing on Jan Masschelein and Maarten Simons, the paper outlines the importance of shared attention to form a public university, which, however, raises questions concerning the relation between speaking subject and listening public in times of problematic social cohesion. It then turns to Jürgen Habermas' theoretical figures of the public to discuss the projective as well as resistant moments of publicness as significant features of communalization in the university. Regarding its transgenerational presuppositions and withdrawals, cohabitation in a university's public can be considered as a matter of ecological and cultural inheritance.